Successful thrombolysis of right heart emboli-in-transit causing cardiac arrest during caesarean section - Supriya Bulchandani; Rabia Imtiaz (Wolters Kluwer Medknow Publications, 2012)
We report a rare case of successful thrombolysis of right heart emboli-in-transit causing cardiac arrest, during caesarean section in a 42-year-old primigravida. This was diagnosed by intra-operative echocardiography. Return to spontaneous circulation was achieved. This was followed by massive post-partum haemorrhage managed conservatively. The lady was discharged home with a Greenfield Inferior Vena Caval filter and Warfarin. Systemic thrombolytic therapy is a challenging decision to make but is usually recommended if it is not contraindicated and the thrombi are demonstrated in more than one cardiac chamber, entailing a higher risk of surgical intervention. However, the potential for massive obstetric bleeding and further side effects must be considered and adequate strategies and resources should be available.